Plamen Pavlov, Ivan Tȋutȋundzhiev, Osmanskite zavoevaniȋa i „Dŭrzhavata na Dukha”. Veliko Tŭrnovo 2017, Izdatelstvo „Abagar”, pp. 231 - Leszka, Mirosław J. (Łódzkie Studia Etnograficzne, 2017)
Recenzja